The neo-governance model of Malaysian Islamic real estate investment trusts / Sr Nor Nazihah Chuweni and Saidah Hamizah Ahmad - Ahmad, Saidah Hamizah (Faculty of Administrative Science and Policy Studies, 2014)
With respect to the unique legal setting and organizational structure under which Islamic Real Estate Investment Trusts (I-REITs) operate, this paper tried to explicate its practiced governance model by wading through the quadrilateral structure: market-centric, relationship-based, transition and emerging governance models. Descriptive analysis and content analysis of Annual Report will be performed to assess the ownership structure, the board of directors, leadership structure and financial statements of the companies to determine the optimal type of model that the I-REITs firms belong to. An attempt has been made to ascertain the type of governance model that best suit Malaysian I-REIT companies’ by using descriptive and content analysis. Since concentrated and pyramidal model are dominant in I-REIT companies, emerging governance model is the best model to characterize Malaysian I-REIT companies.